2023
DOI: 10.1101/2023.04.23.537965
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alpha Synuclein Modulates Mitochondrial Ca2+Uptake from ER During Cell Stimulation and Under Stress Conditions

Abstract: Alpha synuclein (a-syn) is an intrinsically disordered protein prevalent in neurons, and aggregated forms are associated with synucleinopathies including Parkinson' disease (PD). Despite the biomedical importance and extensive studies, the physiological role of a-syn and its participation in etiology of PD remain uncertain. We showed previously in model RBL cells that a-syn colocalizes with mitochondrial membranes, depending on formation of N-terminal helices and increasing with mitochondrial stress. We have n… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 125 publications
(204 reference statements)
0
1
0
Order By: Relevance
“…Alpha-synuclein aggregation is a pathological hallmark of PD. Emerging evidence has shown that alphasynuclein has profound functions at the mitochondria or to impact mitochondria, including mitochondrial oxidative phosphorylation, dynamics, mitophagy, Ca 2+ , and iron homeostasis 7,33,[55][56][57][58][59][60] .…”
Section: Discussionmentioning
confidence: 99%
“…Alpha-synuclein aggregation is a pathological hallmark of PD. Emerging evidence has shown that alphasynuclein has profound functions at the mitochondria or to impact mitochondria, including mitochondrial oxidative phosphorylation, dynamics, mitophagy, Ca 2+ , and iron homeostasis 7,33,[55][56][57][58][59][60] .…”
Section: Discussionmentioning
confidence: 99%